In Utero Stem Cell Transplantation for Radical Treatment of Osteogenesis Imperfecta: Perspectives and Controversies - Amin, Mariam Taher Mohamed; Shazly, Sherif Abd-Elkarim Mohammed (American Journal of Perinatology, 2014)
Osteogenesis imperfecta (OI) is a lethal hereditary connective tissue disease that affects the synthesis of type I collagen. Current treatment options including surgical, physical, and medical treatment help to reduce pain, deformities, and rate of bone fracture. However, these choices are insufficient and are associated with many adverse effects. The development of stem cell therapy allows scientists to consider this option for radical treatment of many genetic diseases including OI. In utero stem cell transplantation provides a better opportunity for early prenatal intervention while the fetus is preimmune and before any permanent damage occurs. Few animal and human trials for treatment of OI have been published, and the results were promising but still controversial. Our objective is to review the available evidence and discuss the points of controversy including the parameters of treatment success and postnatal predictors of long-term treatment outcome.
Keywords: genetic diseases; mesenchymal stem cells; fetal therapy; skeletal anomalies